Nurses’ Social Responsibility and its Relationship with Their Demographic Profiles - Zahra Marziyeh Hassanian (Hamadan University of Medical Sciences, 2017)
Introduction: Social responsibility is decision makers’ commitment to actions that in addition to meeting their interests, provides and enhances well-being in the community. Demographic profiles effect social responsibility. The aim of this study was to determine the status of nurses’ social responsibility and its relationship with their demographic profile.